Cultural Diversity, Innovation, and Entrepreneurship: Firm‐level Evidence from London. (2nd July 2013) - Nathan, Max; Lee, Neil
Abstract A growing body of research is making links between diversity and the economic performance of cities and regions. Most of the underlying mechanisms take place within firms, but only a handful of organization‐level studies have been conducted. We contribute to this underexplored literature by using a unique sample of 7, 600 firms to investigate links among cultural diversity, innovation, entrepreneurship, and sales strategies in London businesses between 2005 and 2007. London is one of the world's major cities, with a rich cultural diversity that is widely seen as a social and economic asset. Our data allowed us to distinguish owner/partner and wider workforce characteristics, identify migrant/minority‐headed firms, and differentiate firms along multiple dimensions. The results, which are robust to most challenges, suggest a small but significant "diversity bonus" for all types of London firms. First, companies with diverse management are more likely to introduce new product innovations than are those with homogeneous "top teams." Second, diversity is particularly important for reaching international markets and serving London's cosmopolitan population. Third, migrant status has positive links to entrepreneurship. Overall, the results provide some support for claims that diversity is an economic asset, as well as a social benefit.